(untitled) (Itinera, 2017)
Three major thinkers of theatre, Erving Goffman, Marvin Carlson and Bruce Wilshire, admit that theatre is an essential and central metaphor for life. Nevertheless, the two main questions of their discussion are, on the one hand, the existence of a range of moral criteria and values that differentiates the two worlds and, on the other, the possibility of defining the threshold between theatre and life.